Effectiveness of Using Wordwall as a Gamification Media in Learning to Increase Student Learning Motivation - Dyan Yuliana; Malika Khoiriyah (ITScience (Information Technology and Science), 2025)
Lack of student motivation is a determining factor in the learning process, thus requiring engaging learning tools that are in line with technological developments favored by students. Wordwall is an educational game that can be utilized as an interactive learning medium. This learning medium boasts many prominent features that are engaging and capable of arousing student motivation and also enabling the creation of interactive activities. These features include crossword puzzles, quizzes, word games, and other games. The research method used was a literature review. The method for searching for article data sources was conducted through the Google Scholar database resources (2022-2024) by retrieving relevant articles published in Indonesian. Key terms and phrases related to wordwall applications, gamification media, and student learning motivation were used in the search for related subjects. The literature search strategy from journals and proceedings used the PICOS framework. The results of this study indicate that Wordwall is effectively used as a gamification medium in learning to increase student motivation, thereby developing students' thinking skills and competitiveness in understanding the material. Furthermore, using Wordwall is also more efficient because it has many game features for designing and reviewing learning assessments that can be played online using a laptop or smartphone anywhere and anytime.